Multi-drug resistant pathogenic Escherichia coli isolated from wild birds, chicken, and the environment in Malaysia - Mohamed, Mohamed Yousif Ibrahim; Abu, Jalila; Zakaria, Zunita; Abdul Rashid Khan; Abdul Aziz, Saleha; Bitrus, Asinamai Athliamai; Habib, Ihab (Multidisciplinary Digital Publishing Institute, 2022)
Transmission of pathogenic microorganisms in the last decades has been considered a significant health hazard and pathogenic E. coli, particularly antibiotic-resistant strains, have long been identified as a zoonotic problem. This study aimed to investigate multidrug resistant pathogenic E. coli isolates from wild birds, chickens, and environment in selected Orang Asli and Malay villages in Peninsular Malaysia. The bacteriological culture-based technique, disc diffusion method, and multiplex Polymerase Chain Reaction (mPCR) assay was used to determine the occurrence of pathogenic E. coli strains in the several samples in the study. E. coli isolates showed a variety of multi-drug resistant (MDR) antibiotypes and Enteropathogenic E. coli (EPEC) and Enteroinvasive E. coli (EIEC) were the most predominantly identified pathogenic E. coli strains. The findings of this study demonstrated the significance of animal reservoirs and the environment as sources of pathogenic E. coli, resistant bacteria, and resistance genes. Hence, there is a need for adoption of a practical surveillance approach on MDR pathogens to control foodborne contamination.